Measuring, Monitoring And Forecasting System For Carbon Monoxide Concentrations [QD181.C1 U85 2005 f rb]. - Raji, Usharani (2005)
The impact of air pollution is broad towards the health of human beings, thus many studies have been focused on the forecasting of air pollutants in urban areas.